2009
DOI: 10.2320/matertrans.mra2008425
|View full text |Cite
|
Sign up to set email alerts
|

Creep Behavior of <I>In Situ</I> Synthesized 7715D Titanium Matrix Composite

Abstract: TiB and TiC reinforced titanium matrix composite was in situ synthesized by consumable vacuum arc remelting and hot-forging based on reaction between titanium, B 4 C powder and graphite powder. The phases were analyzed through X-ray diffraction. The microstructure was examined by means of optical microscopy (OM) and scanning electron microscopy (SEM). Creep behavior was tested at three temperatures: 600 C, 650 C and 700 C respectively within a stress range 100$350 MPa. Class I solution behavior was observed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The relationship between creep rate and stress and temperature can be expressed by the following Equations (1-3) (Li et al, 2008;Wang et al, 2009Wang et al, , 2019:…”
Section: Creep Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The relationship between creep rate and stress and temperature can be expressed by the following Equations (1-3) (Li et al, 2008;Wang et al, 2009Wang et al, , 2019:…”
Section: Creep Propertiesmentioning
confidence: 99%
“…The apparent stress exponents of matrix alloy are lower than those of TMCs. Wang et al (2009) have reported that the creep behavior can be divided into two categories: one creep behavior controlled by viscous dislocation sliding is different; other creep behavior controlled by dislocation climb. Koike et al (1995) report that dislocation sliding is dominant when the stress exponent is 3.5, when the stress exponent is 4.6, dislocation climb is governing.…”
Section: Creep Propertiesmentioning
confidence: 99%
See 3 more Smart Citations